Faithful error: poems - Garrido, Sarah Louise, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2026)
Exploring the tension between freedom and fidelity, Faithful Error meditates on life's most sacred and often difficult loves-romantic, parental, familial, and spiritual-against a backdrop of environmental unease. These poems, rich in natural imagery, trace an emotional journey from intimate contemplation to transcendent questioning, grappling with the value of devotion in a world seemingly designed to extinguish hope. A palpable emotional intensity simmers beneath the restrained language, mirroring the manuscript's central dynamic: a yearning to err, yet ultimately finding freedom in a return-however complicated-to faith.--Provided by publisher.
I. Want for Nothing. The Birds Have Never Failed Me, Part 1 -- Severe -- Tender Forces -- Spring Rains -- Phantom Seed -- Ripen -- Seagulls -- Lake Merritt -- What Was Lost -- The Birds Have Never Failed Me, Part 2 -- II. Feel Free. Forsaken -- Holy Confines -- Finally -- Evergreen -- Perfect Meeting -- Finally Free -- Catechism -- Oxalis -- The Choice -- Aquarium -- What the Tide Takes, What the Tide Leaves -- III. For the Taking. The Cold Lord -- That Old Horse -- Cross Over -- Prayer for Our Children -- Blessed Assurance -- News at Dawn -- The Flood -- Tangerines -- Your Loss -- If (Breath) -- The Dreams -- The Robins -- Now -- IV. A Fruit Compelled. The World s Work -- Another Perspective -- Abide -- Fleeting -- To Last (If Only) -- The Burden of Proof -- Signs -- The Word -- You Drew Me Out -- Before It Ends -- Beyond -- You Were Always There.